2021
DOI: 10.1002/saj2.20310
|View full text |Cite
|
Sign up to set email alerts
|

Split application of nutrients improve growth and yield of Huanglongbing‐affected citrus trees

Abstract:  Split application of ground applied essential nutrients increase the availability of nutrients and decrease higher nutrient requirements. Split application of essential nutrients improves the availability and uptake of nutrients for adversely affected HLB-induced root density citrus trees, thus decrease leaching and reduce downstream ecosystems. The availability of essential nutrients increases vegetative growth. Vegetative growth improves fruit yield and quality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 56 publications
0
15
0
Order By: Relevance
“…Atta et al [47] found that trees treated with 2× the recommended Mn, Zn, and B in a foliar and ground application mix had improved root lifespan of field grown sweet orange trees. In addition, another study by Atta et al [48] found that split ground application of 224 kg ha −1 of N, foliar application of N at 9 kg ha −1 , and 9 kg ha −1 of ground applied Mn and Zn improved physiology and yield of field grown HLB-affected sweet orange trees.…”
Section: Discussionmentioning
confidence: 96%
“…Atta et al [47] found that trees treated with 2× the recommended Mn, Zn, and B in a foliar and ground application mix had improved root lifespan of field grown sweet orange trees. In addition, another study by Atta et al [48] found that split ground application of 224 kg ha −1 of N, foliar application of N at 9 kg ha −1 , and 9 kg ha −1 of ground applied Mn and Zn improved physiology and yield of field grown HLB-affected sweet orange trees.…”
Section: Discussionmentioning
confidence: 96%
“…Excessive application of P on sandy soils beyond the recommended rate in HLB-infected citrus groves could result in P leaching and runoff, which eventually plays a vital role in the eutrophication of surface water bodies [ 18 ]. However, in a split application study of essential nutrients conducted at Immokalee, FL during the 2017–2019 growing seasons, leaf P was within the optimum range without the addition of any P to the soil during any season of the study [ 19 ].…”
Section: Nutrient Management Of Hlb-infected Sweet Oranges Treesmentioning
confidence: 99%
“…Meanwhile, the leaf Mg concentration was below the optimum range in HLB-infected trees. However, putting Mg as thiosulfate on the ground increased the amount of Mg in the leaves and kept it within the best ranges [ 19 , 31 , 33 , 42 ].…”
Section: Nutrient Management Of Hlb-infected Sweet Oranges Treesmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the use of precise irrigation scheduling and fertigation management strategies should be the focus of studies in stimulating citrus root improvement, water and nutrient uptake efficiency, and growth of HLB-infected citrus trees on Florida's sandy soils. Hence, split application of essential nutrients has been studied as a therapeutic effect in HLB-affected citrus trees so that nutrients will be available in the root zone during the entire growing season [5,16,17].…”
Section: Introductionmentioning
confidence: 99%